A Comparative Analysis of the Teachings of Bodhidharma and Butthan: A Brief Overview of Philosophies, Origins and Significance - Yuree, Md Anwar Kamal (ILAM इलम, 2025)
This article explores the ancient and intangible development of psychophysical transformative practices, tracing their progress from the teachings of Bodhidharma, who is also credited with founding Zen and the systematic form of self-defense. He is credited with introducing contemplative and physical training to the famous Shaolin monks, linking it to the contemporary discipline of Butthan, a martial art and combat sport with distinctive approaches to personal development. Bodhidharma’s teachings and philosophy in balanced physical and mental training are reflected in the evolution of Butthan’s unique approaches to transformative psychophysical systems in the modern world. Through qualitative analysis, where researcher has introduced a narrative approach to examine the flow, adaptation, and revolutions within these performances that aim to harmonize mind and body for greater well-being, resilience, and holistic growth. The article also highlights the metaphysical reinforcements, cultural contexts, and applications of these practices in present-day life.